Algae obscura: The potential of rare species as model systems. Issue 2 (9th March 2023) - Van Etten, Julia; Benites, Luiz Felipe; Stephens, Timothy G.; Yoon, Hwan Su; Bhattacharya, Debashish
Abstract: Model organism research has provided invaluable knowledge about foundational biological principles. However, most of these studies have focused on species that are in high abundance, easy to cultivate in the lab, and represent only a small fraction of extant biodiversity. Here, we present three examples of rare algae with unusual features that we refer to as "algae obscura." The Cyanidiophyceae (Rhodophyta), Glaucophyta, and Paulinella (rhizarian) lineages have all transitioned out of obscurity to become models for fundamental evolutionary research. Insights have been gained into the prevalence and importance of eukaryotic horizontal gene transfer, early Earth microbial community dynamics, primary plastid endosymbiosis, and the origin of Archaeplastida. By reviewing the research that has come from the exploration of these organisms, we demonstrate that underappreciated algae have the potential to help us formulate, refine, and substantiate core hypotheses and that such organisms should be considered when establishing future model systems.